Meningkatkan Pemahaman Tentang Pentingnya Itsbat Nikah dalam Perkawinan Siri di Desa Bukit Baling Kecamatan Sekernan Kabupaten Muaro Jambi - Evalina Alissa; Faizah Bafadhal; Suhermi Suhermi; Meri Yarni; Diana Amir (CV. Ulil Albab Corp, 2024)
Itsbat Nikah (Legalization of Marriage) is a determination of the marriage of husband and wife which has been carried out in accordance with the provisions of the Islamic religion with the fulfillment of the conditions and pillars of marriage, but the marriage has not been or has not been registered with the authorized official, namely the Religious Affairs Office official, in this case the Marriage Registrar Officer. The marriage regulations determined by the Religious Courts have a very big role and contribution in efforts to provide a sense of justice and legal certainty for married couples who do not yet have a marriage book as authentic proof or married couples who carry out unregistered marriages. By stipulating the marriage law, husband and wife will receive their rights as full citizens, including recognition of their children. Community service activities in Sekernan Subdistrict, Muaro Jambi Regency with the theme of increasing understanding of the importance of the Itsbat Nikah in unregistered marriages to increase public insight into the procedures for applying for the Itsbat Nikah related to unregistered marriages which are still found in society for various reasons so that husband and wife are not have a marriage certificate or marriage book. This Community Service Activity was carried out on August 15 2023 at the Office of the Head of Bukit Baling Village, Sekernan District, Muaro Jambi Regency and was attended by the community and local village officials. This service is carried out using lecture, discussion and question and answer sessions.